2008
DOI: 10.1111/j.1365-2125.2008.03199.x
|View full text |Cite
|
Sign up to set email alerts
|

The ability of atropine to prevent and reverse the negative chronotropic effect of fingolimod in healthy subjects

Abstract: WHAT IS KNOWN ABOUT THIS SUBJECT• Clinical pharmacology and clinical therapeutic studies of fingolimod demonstrate that heart rate after the initial dose decreases by about 10-20% while normal circadian rhythm is preserved. With continued daily dosing, heart rate returns to normal over the next 2 weeks. • This negative chronotropic effect is consistent with the binding of fingolimod-phosphate to the sphingosine-1-phosphate receptor on atrial myocytes. WHAT THIS STUDY ADDS• The present clinical pharmacology stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…3B). Results with human patients indicate that the equilibrium between FTY720 and its phosphate rests more heavily in favor of dephosphorylation: the plasma concentration of FTY-P drops below that of FTY720 12 to 24 h after a single 5-mg dose of FTY720; thereafter, FTY-P declines as a proportion of the FTY720 concentration (Kovarik et al, 2008(Kovarik et al, , 2009. On this basis, one would predict that AAL(R) would achieve effective immunosuppression at a significantly lower dose in humans than FTY720.…”
Section: Discussionmentioning
confidence: 88%
“…3B). Results with human patients indicate that the equilibrium between FTY720 and its phosphate rests more heavily in favor of dephosphorylation: the plasma concentration of FTY-P drops below that of FTY720 12 to 24 h after a single 5-mg dose of FTY720; thereafter, FTY-P declines as a proportion of the FTY720 concentration (Kovarik et al, 2008(Kovarik et al, , 2009. On this basis, one would predict that AAL(R) would achieve effective immunosuppression at a significantly lower dose in humans than FTY720.…”
Section: Discussionmentioning
confidence: 88%
“…S1P 1 has been shown to regulate sinus bradycardia, is coupled to G protein-coupled inwardly-rectifying potassium (Guo et al, 1999), and is responsible for the atropine sensitive vagal sinus bradycardia (Kovarik et al, 2008;Fryer et al, 2012;Legangneux et al, 2013). S1P 3 in mice has rich expression at the mRNA level on cells of neural crest origin (Meng and Lee, 2009) and was recently shown to be transcriptionally present along S1pr1 and S1pr2 transcripts in the AVN of rats.…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 treatment has additionally revealed an increased incidence of atrioventricular (AV) disturbances during the first dose, including AV block and asystole, particularly in subgroups of patients with preexisting cardiac conditions that require other therapeutics, i.e., beta blockers and calcium channel blockers, to maintain adequate cardiovascular dynamics (Vanoli et al, 2014). Atropine reversal of the sinus bradycardia (Kovarik et al, 2008) and the demonstration of sinus bradycardia with S1P 1/5 -selective agonists in humans (Legangneux et al, 2013) as well as rodents (Fryer et al, 2012) suggest that sinoatrial node (SAN) effects and those events resulting from alterations in AV-nodal conduction might be distinctly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…There were no episodes of symptomatic bradycardia occurring beyond 24 hours, and no clinically significant effect on heart rate was observed with sustained administration of the drug 46,47. Although during clinical trials, pharmacological treatment has never been required to treat bradycardia, it has been suggested that intravenous atropine can ameliorate the negative effect of fingolimod on cardiac rhythm 49. In addition to transient changes in cardiac rhythm, fingolimod induced cardiac conduction abnormalities, including first- and second-degree atrioventricular block.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%